Outbreak of occupational Brucella infection caused by live attenuated Brucella vaccine in a biological products company in Chongqing, China, 2020. Issue 1 (31st December 2022) - Zhou, Chunbei; Huang, Wenli; Xiang, Xu; Qiu, Jianping; Xiao, Dayong; Yao, Ning; Shu, Qiang; Zhou, Shuang
ABSTRACT: The northern areas of China are traditional endemic regions for brucellosis in both animals and humans, while occasional outbreaks of brucellosis have been observed in neglected southern provinces. On 16 December 2020, Chongqing Center for Disease Control and Prevention (CQCDC) received a report of 15 Brucella seropositive employees in a biological products company. The CQCDC and the local health administrative department launched an investigation that included identification of cases, laboratory testing of samples, and employees' interview to identify the cause of this incident. A case-control study was implemented to compare high-risk factors between cases and serology-negative personals. Human and animal serum samples and environmental swabs were collected for testing. A total of 61 recessive infectors were found with an infection rate of 43.57% (61/140). Fisher's exact test showed that there were significant differences in Brucella infection rates among different post classifications ( p  = 0.02), working places ( p  = 0.007), and buildings ( p  < 0.0001). Case-control study showed that working in vaccine production workshop was independently associated with an increased risk of infection (odds ratio ( OR ): 2.60; 95% confidence interval ( CI ): 1.31–5.19). The positive detection rate was 88.06% (59/67) for production environment and 16.67% (2/12) for external environment. The investigation indicated that close contact with biological products and aerosol were the potential transmission routes of this outbreak under the condition of insufficient personal protection and disinfection. Our study provides new epidemiological evidence for a more detailed understanding of occupational infections with live attenuated Brucella vaccine.